2021
DOI: 10.21037/atm-20-4708
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, osteopenia, osteoporosis, and fracture risk in patients with atopic dermatitis: a systematic review and meta- analysis

Abstract: Background: The relationship between atopic dermatitis (AD) and abnormal bone metabolism remains unclear. We performed a systematic review and meta-analysis to determine whether patients with AD were associated with increased risks of low bone mineral density (BMD), osteopenia, osteoporosis, and related fractures.Methods: We searched PubMed, Embase, and the Cochrane Library through December 2019 to identify studies that investigated the association between AD and abnormal bone metabolism (including BMD, osteop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Osteoporosis is a systemic skeleton disease characterized by an imbalance of bone metabolism and high risk of fractures, whose clearly fundamental pathophysiological is mechanical microenvironment. 1 , 2 As an age-related disease, osteoporosis has multiple similar characteristics with diabetes, cardiovascular disease and fractures that affects an estimated 44 million Americans over the age of 50 years, leading to significant morbidity, mortality, and disability all over the world. 3 , 4 However, the clear understanding of associated characteristics between osteoporosis and body metabolism has not been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a systemic skeleton disease characterized by an imbalance of bone metabolism and high risk of fractures, whose clearly fundamental pathophysiological is mechanical microenvironment. 1 , 2 As an age-related disease, osteoporosis has multiple similar characteristics with diabetes, cardiovascular disease and fractures that affects an estimated 44 million Americans over the age of 50 years, leading to significant morbidity, mortality, and disability all over the world. 3 , 4 However, the clear understanding of associated characteristics between osteoporosis and body metabolism has not been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the more frequent use of systemic corticosteroids in severe AD in the past, it is not surprising that, in the current study, severe AD increased the risk of osteoporosis and drug-induced cataract. Both conditions are previously reported comorbidities of AD and known adverse effects of systemic corticosteroids (29,30). How ever, an earlier study by Haeck et al (31) found that lower bone density in patients with AD was independent of corticosteroid use within the previous 5 years; hence other explanations are possible.…”
Section: Discussionmentioning
confidence: 90%
“…The possible mechanisms may involve inflammation-induced bone loss, corticosteroid exposure, dietary restrictions due to food allergies, etc. 25 A nationwide population-based study in Taiwan also showed that the incidence of osteoporosis was 4.72-fold greater in AD patients than in non-AD patients. 26 Another example is psoriasis.…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review and meta‐analysis demonstrated that patients with atopic dermatitis (AD) are at increased risk of osteoporosis and related fractures. The possible mechanisms may involve inflammation‐induced bone loss, corticosteroid exposure, dietary restrictions due to food allergies, etc 25 . A nationwide population‐based study in Taiwan also showed that the incidence of osteoporosis was 4.72‐fold greater in AD patients than in non‐AD patients 26 .…”
Section: Discussionmentioning
confidence: 99%